Fenomena PHK Masa Pandemi Covid-19 dan Dampaknya Terhadap Fresh Graduate Jurusan Ilmu EKonomi Universitas Negeri Surabaya - Rizqiya Fauziyah Akhmad; Lucky Rachmawati (Jurnal Ekonomika : INDEPENDEN, 2021)
This research was conducted to discuss the impact that occurred due to the termination ofemployment (PHK) by companies due to the COVID-19 pandemi on jobseekers, especiallyfresh graduates at the Department of Economics, Universitas Negeri Surabaya.. TheCOVID-19 pandemi has had a significant impact on several aspects such as economic andemployment aspects, with the layoff policy in this pandemi era, as well as the unstable stateof the economy, causing unemployment to increase. The method used in this research isdescriptive qualitative method with a phenomological approach. The results of the studyare based on the results of interviews that have been conducted with the informants andare also compared with previous theories and studies. Freshgraduate majoring inEconomics, State Universitas Negeri Surabaya as a jobseeker felt the impact of thecompany's policy of layoffs during the COVID-19 pandemi. Hard skills and soft skills arethe main foundation for competing in the world of work and the creation of superior humanresources in the midst of today's global changes. Keywords: COVID-19, freshgraduate, PHK, unemployment